Improved accuracy of cardiac output estimation by the partial CO2 rebreathing method. - Kotake Y; Yamada T; Nagata H; Suzuki T; Serita R; Katori N; Takeda J; Shimizu H; Kotake, Yoshifumi; Yamada, Takashige; Nagata, Hiromasa; Suzuki, Takeshi; et al. (Journal of Clinical Monitoring & Computing, 2009)
Objective: This study investigated the accuracy of the NICO monitor equipped with the newer software. Additionally, the effects of the increased dead space produced by the NICO monitor on ventilatory settings were investigated.Methods: Forty-two patients undergoing elective aortic reconstruction participated in this prospective, observational study at a university hospital. Cardiac output was continuously monitored using both the NICO monitor and continuous cardiac output (CCO) measured by a pulmonary artery catheter. A NICO monitor equipped with ver. 4.2 software was used for the first 21 patients while a NICO monitor equipped with ver. 5.0 software was used for the rest of the patients. Cardiac output measured by bolus thermodilution (BCO) at 30 min intervals was used as a reference.Results: The bias +/- precision of the NICO monitor was 0.18 +/- 0.88 l/min with ver. 4.2 software (n = 182) and 0.18 +/- 0.83 l/min with 5.0 software (n = 194). The accuracy of the NICO monitor is comparable to CCO, whose bias +/- precision against BCO is 0.19 +/- 0.81 l/min (n = 376). At the same level of CO(2) production and minute ventilation, PaCO(2) was lower in the patients monitored by NICO with ver. 5.0 software than patients with ver. 4.2 software.Conclusions: This study demonstrated the improved performance of the NICO monitor with updated software. The performance of the NICO monitor with ver. 4.2 or later software is similar to CCO. However, the cardiac output measurement did not fulfill the criteria of interchangeability to the cardiac output measurement by bolus thermodilution. Updates to ver. 5.0 attenuated the effects of rebreathing introduced by the NICO monitor without compromising the accuracy of the cardiac output measurement.